REPORTS: RESEARCH PROJECTS IN THE MCGILL FACULTY OF EDUCATION - Pedersen, Eigil; Anderson, Gary J. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1969)
Research is rapidly gaining in importance at McGill's Faculty of Education. One evidence of this is the establishment of a Department of Educational Research; another is the great increase in the number of research projects now under way. Research at the Faculty of Education receives financial support from a number of sources. Among the most important of these are the Canada Council and the Institute of Research in Education of the Province of Quebec. The following brief reports are of research projects, under way or recently completed, supported by these two agencies. It is our intention to present information about other research activities from time to time in this Journal. In so doing, we invite readers who are interested in particular projects to communicate with the researchers directly.